2015
DOI: 10.1016/j.acap.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Provider Prompts on Adolescent Immunization Rates: A Randomized Trial

Abstract: In both a local and national setting, provider prompts failed to improve adolescent immunization rates. More rigorous practice-based changes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 26 publications
(36 reference statements)
0
67
1
Order By: Relevance
“…8,9 Captured opportunities increased after decisions by providers to use consistent language to describe the HPV vaccine, focus on cancer prevention, and emphasize vaccination at acute visits. The project was completed at a modest cost, similar to the cost per clinician of attending a continuing education conference, with the greatest expense the time invested by participating pediatricians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Captured opportunities increased after decisions by providers to use consistent language to describe the HPV vaccine, focus on cancer prevention, and emphasize vaccination at acute visits. The project was completed at a modest cost, similar to the cost per clinician of attending a continuing education conference, with the greatest expense the time invested by participating pediatricians.…”
Section: Discussionmentioning
confidence: 99%
“…7 Missed opportunities persisted, however, as they have in other studies. 9 These results underscored the need for continued improvement.…”
mentioning
confidence: 90%
“…Electronic health record (EHR) systems can automate reminder-recalls for patients due for HPV vaccination, generate reminder prompts for providers to administer the vaccine, and help facilitate nurse-only immunization visits and walk-in immunization hours that can make completion of the HPV vaccine series easier. Strategies such as reminder-recalls for patients and reminder prompts for providers have often, but not always, been successful at increasing rates of vaccination, 7,8 but implementation of these strategies is inconsistent. In addition, EHRs can generate reports to track the effect of strategies to increase HPV vaccination and potential procedural challenges during implementation (eg, vaccine supply, parents refusing or delaying vaccination, etc).…”
Section: System-level Approachesmentioning
confidence: 99%
“…27 In addition to the studies described above that combined assessment and feedback with provider reminders, 22,25,27 1 study investigated the effect of provider reminders alone. 29 This study found no effect of electronic health record provider prompts on HPV vaccine initiation or completion in females compared to a standard of care control group.…”
Section: Provider Assessment and Feedback And Provider Remindersmentioning
confidence: 53%